Early Detection of Pancreatic Cancer - Eguia, Vasco; Gonda, Tamas Adam; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2012)
Despite treatment advances pancreatic cancer remains one of the most lethal malignancies. It is expected that early detection and screening of high risk patient population may have the most significant impact on altering overall survival in this disease. Serologic biomarkers may be the most useful in early detection and histology-based markers may have the most significant role in differentiating benign, pre-malignant and malignant lesions. Here we review several serum and tissue-based biomarkers and summarize new data presented at the 2012 ASCO Gastrointestinal Cancers Symposium (Abstracts #151, #164, #188) on the potential role of PAM4 in pancreatic cancer screening and diagnosis.